Motif Sarjana Non Keguruan Untuk Menjadi Guru di Kelurahan Tanjung Berlian Kota Kecamatan Kundur Utara - Nurapitasari Nurapitasari; Nanik Rahmawati; Siti Arieta (Faculty of Social and Political Science Universitas Maritim Raja Ali Haji, Indonesia, 2023)
One of the advancements of a country in educating the life of every nation, school is a place to get education, where every school cannot be separated from the role of a qualified, responsible teacher to carry out learning. The teaching profession is of great interest to the undergraduate community (S1), so there is a mismatch in the background of the teaching profession. The purpose of this study was to find out the motives of non-teacher graduates to become teachers in Tanjung Berlian Village, Kota Kundur Utara District. This research uses a qualitative descriptive approach. Research informants are teachers, principals, parents of students. The theory used in this research is social mobility. The results of the research are seen from the indicators, namely 1) job opportunities, namely by having a school where the teaching profession is needed, so that it becomes a job opportunity for bachelor's degrees (S1). 2) Social status, that is, with minimal parental background, the teaching profession is needed in educating, teaching, and guiding their children. So that the teaching profession has a high position, the community environment.